Prophylactic antibiotics to prevent surgical site infections in Botswana: findings and implications. Issue 3 (27th May 2018) - Mwita, Julius C.; Souda, Sajini; Magafu, Mgaywa G. M. D.; Massele, Amos; Godman, Brian; Mwandri, Michael
ABSTRACT: Objectives : Antibiotic prophylaxis in surgery is known to reduce the rate of surgical site infections (SSI) as well as shorten hospital stay. However, there is currently a scarcity of data on antibiotic prophylaxis and SSIs among African countries including Botswana. Consequently, this study aimed to address this. Methods : A prospective study involving 400 patients was carried out at a leading tertiary hospital in Botswana from 2014–2015. Patients' demographic information, type of surgery performed and peri-operative use of antibiotics were documented. All enrolled patients were followed-up for 30 days post discharge to fully document the incidence of SSIs. Results : Median age of patients was 35.5 (25 – 50) years, with 52% female. There were 35.8% emergency and 64.2% elective surgeries. The most common operations were exploratory laparotomy (25%), appendectomy (18.3%), excision, and mastectomy (8%). Antibiotics were given in 73.3% of patients, mainly postoperatively (58.3%). The most commonly prescribed antibiotics were cefotaxime (80.7%), metronidazole (63.5%), cefradine (13.6%) and amoxicillin/clavulanate (11.6%). The incidence of SSI was 9%. The most common organisms were Pseudomonas aeruginosa, Staphylococcus aureus, and coagulase-negative staphylococci. Conclusion : The rate of SSI is a concern, and may be related to inappropriate antibiotic prophylaxis given post operatively. Interventions are in place to decrease SSI rates to acceptable levels in this leading hospital by improving for instance infection prevention practices including the timing of antibiotic prophylaxis. Research is also ongoing among other hospitals in Botswana to reduce SSI rates building on these findings.